2021
DOI: 10.1108/apjml-11-2020-0820
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the antecedents and outcomes of brand community-swinging in a poly-social-media context: a perspective of channel complementarity theory

Abstract: PurposeThis study aims to examine the increasingly widespread phenomenon of brand community-swinging, which refers to a user's routine use of multiple brand communities of a brand across different social media. Drawing from channel complementarity theory, this study examines whether the complementarity of gratifications in four values (i.e. information value, entertainment value, social interaction value and self-presentation value) influences brand community-swinging and, in turn, cultivates brand loyalty.Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 90 publications
(119 reference statements)
0
21
0
2
Order By: Relevance
“…However, social media platforms enable consumers to participate in multiple virtual brand communities simultaneously (Phua et al, 2017;Pelletier et al, 2020). For example, Liao et al (2022) examined the effect of four values on the consumers' community-swinging behaviors. However, consumer engagement in multi-competing brand communities has not been adequately emphasized and studied (Thompson et al, 2016(Thompson et al, , 2019.…”
Section: Theoretical Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, social media platforms enable consumers to participate in multiple virtual brand communities simultaneously (Phua et al, 2017;Pelletier et al, 2020). For example, Liao et al (2022) examined the effect of four values on the consumers' community-swinging behaviors. However, consumer engagement in multi-competing brand communities has not been adequately emphasized and studied (Thompson et al, 2016(Thompson et al, , 2019.…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…The openness of third-party social media platforms enables users to participate in various brand communities at will to obtain product information or engage in social interactions and even switch between different brand communities ( Tandoc et al, 2019 ). An increasing number of scholars have found that instead of participating in a single brand community, a large number of consumers tend to participate in and navigate through different brand communities belonging to multiple brands within an industry, even the competing brands ( Thompson and Sinha, 2008 ; Tan and Lee, 2015 ; Thompson et al, 2016 ; Liao et al, 2022 ). This phenomenon is defined as “multi-competing brand community engagement” (MBCE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a relatively new phenomenon, social commerce has evolved quickly in practice and academic research (Xiao et al, 2015;Ko, 2020;Liao et al, 2022). The social commerce community is a marriage of transactional and social that enables its members to get their fans and followers shopping by making the whole selling process social.…”
Section: Findings and Contributionsmentioning
confidence: 99%
“…Liao et al conducted a quantitative study to examine how factors (e.g., information value) influence consumers’ swinging behavior and cultivates brand loyalty. It was found that information value, social interaction value and self-presentation value had significantly positive impacts on consumers’ brand community-swinging, which further fosters brand loyalty [ 42 ]. Bolye et al examined the accuracy of self-reported computer-specific time on multiple social media platforms and evaluated the influencing factors of reported accuracy based on platform swinging context [ 43 ].…”
Section: Introductionmentioning
confidence: 99%